Electrochemical reactivity and proton transport mechanisms in nanostructured ceria. (13th July 2016) - Ding, J; Strelcov, E; Kalinin, S V; Bassiri-Gharb, N
Abstract: Electrochemical reactivity and ionic transport at the nanoscale are essential in many energy applications. In this study, time-resolved Kelvin probe force microscopy (tr-KPFM) is utilized for surface potential mapping of nanostructured ceria, in both space and time domains. The fundamental mechanisms of proton injection and transport are studied as a function of environmental conditions and the presence or absence of triple phase boundaries. Finite element modeling is used to extract physical parameters from the experimental data, allowing not only quantification of the observed processes, but also decoupling of their contributions to the measured signal. The constructed phase diagrams of the parameters demonstrate a thermally activated proton injection reaction at the triple phase boundary, and two transport processes that are responsible for the low-temperature proton conductivity of nanostructured ceria.